Scotland and the borders of romanticism - Davis, Leith 1960-; Duncan, Ian 1955-; Sorensen, Janet (Cambridge University Press, 2004)
Originally published in 2004, Scotland and the Borders of Romanticism is a collection of critical essays devoted to Scottish writing between 1745 and 1830 - a key period marking the contested divide between Scottish Enlightenment and Romanticism in British literary history. Essays in the volume, by leading scholars from Scotland, England, Canada and the USA, address a range of major figures and topics, among them Hume and the Romantic imagination, Burns's poetry, the Scottish song and ballad revivals, gender and national tradition, the prose fiction of Walter Scott and James Hogg, the national theatre of Joanna Baillie, the Romantic varieties of historicism and antiquarianism, Romantic Orientalism, and Scotland as a site of English cultural fantasies. The essays undertake a collective rethinking of the national and period categories that have structured British literary history, by examining the relations between the concepts of Enlightenment and Romanticism as well as between Scottish and English writing